Estimation of Effective Dose and Excess Lifetime Cancer Risks due to Ingestion of Natural Radionuclides in Rice Samples from Selected Farms in Southwestern Nigeria - Arije, O. T.; Ayodele, A. E.; Olubi, O. E. (Ankara Üniversitesi Nükleer Bilimler Enstitüsü, 2022)
This study was carried out to evaluate the radioactivity concentrations of 40K, 232Th and 238U in ten rice samples of the same species collected from different rice farms across Ondo and Ekiti States, southwestern Nigeria. The activity concentration measurements were determined using n–type co-axial HPGe detectors. In samples from one of the states (Ondo), the activity concentration was found to vary from 36.04 - 2139.35 Bq∙kg-1 for 40K, 0.12 - 79.23 Bq∙kg-1 for 232Th and 0.22 - 83.36 Bq∙kg-1 for 238U. In the other state (Ekiti), the value was found to vary from 3.99 - 2078.91 Bq∙kg-1 for 40K, 5.18 - 73.82 Bq∙kg-1 for 232Th and 14.50 - 83.21 Bq∙kg-1 for 238U. The mean annual effective dose to adults from the consumption of the rice were obtained as 0.93 and 0.84 mSv∙y -1 with excess lifetime cancer risk (ELCR) calculated to be 2.98 x 10-10 and 2.56 x 10-10 for Ondo and Ekiti, respectively. The values were compared with the internationally acceptable limits and were found to be lower compared to the acceptable world average ELCR value of 0.29 x 10–3 for radiological risk to the public by UNSCEAR. The rice samples from the locations are safe for human consumption.
Keywords: Radioactivity, Rice, Effective ingestion dose, Gamma spectroscopy, Excess life time cancer risk